A cross sectional survey assessing knowledge, attitude and practices regarding antibiotic resistance among 2nd, 3rd and final year MBBS students in a teaching hospital in Navi Mumbai (Funded Work) - YADAV P; DEOLEKAR P; SYED A; SHARMA N; SURI R; ISTUTI K (International Journal of Pharma and Bio Sciences, 2019)
In 2011, the theme of World Health Day as ‘Combat Antimicrobial Resistance was given No Action Today, No Cure Tomorrow’. The is a serious and global problem of antibiotic abuse and there is a growing need to urgently develop new strategies for the prevention of resistance of bacteria to antibiotics. The aim of this study is to evaluate the current knowledge, attitude, and practices regarding antibiotic use and antibiotic resistance (ABR) among the healthcare profession students at a Medical college. This study is a cross-sectional, questionnaire based survey. The validated questionnaire was distributed among 150 MBBS students from 2nd, 3rd, and final year. students and the results were presented in the form of graphs and tables. 94% of the 2nd year students knew that bacteria was not responsible for the common cold and influenza The knowledge of the final year in most of the questions were 100%. The final year students had a positive attitude towards ABR and antibiotics however the attitude of the 2nd year and 3rd year was found to be more casual. Practices of the final year students were found to be more sensible,100% of the students consult a doctor before starting an antibiotic except for the fact that 94% of the students stop taking the further treatment once they start feeling better after taking antibiotics. 98% of students from 2nd year believe indiscriminate antimicrobial use leads to the emergence of the growing problem of resistance. Our study provides important views regarding the knowledge, attitudes and practices about antibiotic resistance and its use among the future doctors. It revealed that most of the students were aware of antimicrobial resistance and its consequences. The only concern was their casual attitude regarding antibiotic use. This was an ICMR- STS approved project.